Influence of Environment-based Learning Materials to Improve the Eco-literacy of PGSD Students - Arga, Hana Sakura Putu; Rahayu, Galih Dani Septiyan (Mimbar Sekolah Dasar, 2019)
Human concern on the environment is unfortunately seen decreasing, which has resulted in negative environmental damages caused by human actions. To address this issue, this research seeks to see the influence of environment-based teaching materials in social studies learning to improve the eco-literacy of students of primary school teacher education (PGSD, Pendidikan Guru Sekolah Dasar) study program. This research involved third semester 60 PGSD students of a private university in Bandung Regency, Indonesia. Therefore, this research investigated the differences of environment-based learning materials and conventional learning in improving the eco-literacy of PGSD students. This research used a quasi-experimental method with nonrandomized pretest-posttest control group design and used quantitative observation instruments in the form of checklists to obtain the data. The results revealed that by using environment-based learning resources, the social studies learning could improve the eco-literacy of PGSD students, and was considered better than implementing conventional learning.